Why Construction Industry Productivity Is Declining - Allen, Steven G. (The Review of Economics and Statistics, 1985)
According to unpublished data compiled by BLS, productivity in the construction industry reached a peak in 1968 and, except for a brief and small upturn between 1974 and 1976, has been falling ever since. This paper examines the sources of this productivity decline between 1968 and 1978 by estimating a production function to assign weights to various factors responsible for productivity change and deriving a new price deflator for construction which does not rely on labor or material cost indexes, thus eliminating a systematic bias toward overstating the rate of growth of prices.